Vascular Tortuosities of the Upper Eyelid: A New Clinical Finding in Fabry Patient Screening - Langis Michaud (Journal of Ophthalmology)
Purpose. To report a new clinical finding related to Fabry disease. Methods. Fabry subjects were enrolled in the study, matched for age and sex with healthy individuals as a control group. This is a prospective review of all upper lid pictures taken for every subject at their last visit. A 4-step grading scale is proposed to classify this new entity. Results. Group A (Fabry) comprised 16 males and 22 females, aged 40 (±14) years on average. Group B (control) comprised 7 males and 8 females, aged 37 (±12) Vessels tortuosity was identified on the external superior lid in 36 of the Fabry patients (94.7%), while none of the subjects in group B showed similar vessels tortuosity. In addition, microaneurysms (MAs) were found in 10/38 group A subjects while none in group B presented a similar finding. The differences are highly significant. Conclusion. This paper proposes that blood vessels tortuosity on the upper eyelid be recognized as a new clinical entity for inclusion among the classic ocular manifestations of Fabry’s disease. Without evidence of any negative impact, it should be considered a benign sign contributing to evidence of suspected Fabry disease.